Elementary School The Influence of Mental Training on Volleyball Team Performance at SMA 13 Makassar - Muhammad Qasash Hasyim (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Volleyball is a team sport that requires optimal physical and mental coordination. The mental aspect in sports is often overlooked even though it has an important role in determining the performance of athletes. The SMA 13 Makassar volleyball team experienced a decline in performance in regional competitions which was allegedly caused by psychological factors such as anxiety, lack of concentration, and low confidence. This study aims to analyze the influence of mental training on the performance of the volleyball team at SMA 13 Makassar and identify the mental aspects that have the most influence on improving team performance. This study uses a quasi-experimental design with a pretest-posttest control group design approach. The subjects of the study were 24 students who were members of the volleyball team of SMA 13 Makassar which were divided into an experimental group (n=12) and a control group (n=12). The experimental group received 8 weeks of mental training with a frequency of 3 times per week, while the control group received only physical training and conventional techniques. The instruments used included volleyball technique performance tests, sports anxiety scale (SAS-2), athlete confidence scale (TSCI), and concentration test (d2 test). Data analysis used paired sample t-test and independent sample t-test with significance level of α = 0.05. The results showed that there was a significant difference in the performance of the volleyball team between the experimental group and the control group after the provision of mental training (p < 0.05). The experimental group showed significant improvements in serving accuracy (from 68.5% to 84.2%), passing accuracy (from 72.3% to 88.7%), spike effectiveness (from 65.8% to 82.4%), and blocking quality (from 58.9% to 76.3%). The psychological aspect also experienced significant improvement with a decrease in anxiety levels (from 3.4 to 2.1), an increase in self-confidence (from 3.2 to 4.3), and an increase in concentration (from 78.5 to 92.1). Mental training has proven to be effective in improving the performance of the volleyball team at SMA 13 Makassar. Structured mental training programs can be an alternative training method to optimize the potential of young athletes in the sport of volleyball.